2019
DOI: 10.1016/j.ejmg.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic c.181_183delTGT in BTB domain of KLHL7 is associated with overlapping phenotypes of Crisponi/CISS1-like and Bohring-Opitz like syndrome

Abstract: Biallelic pathogenic variants in KLHL7 are known to result in Crisponi syndrome (CS)/cold-induced sweating syndrome type 1 (CISS1) like phenotype and Bohring-Opitz-like syndrome. In this report, a trio whole-exome sequencing (WES) was performed in proband with cold-induced sweating, microcephaly, facial dysmorphism, spasticity, failure to thrive, pigmentary abnormalities of the retina, hypoplasia of corpus callosum and periventricular nodular heterotopia. A novel homozygous in-frame deletion was identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Recently, individuals with an overlapping phenotype of CS/CISS, BOS and/or RP caused by KLHL7 variants were identified. Hence, physicians have to be aware of the range of variability in presentation of individuals with KLHL7 variants …”
Section: Differential Diagnosticmentioning
confidence: 99%
“…Recently, individuals with an overlapping phenotype of CS/CISS, BOS and/or RP caused by KLHL7 variants were identified. Hence, physicians have to be aware of the range of variability in presentation of individuals with KLHL7 variants …”
Section: Differential Diagnosticmentioning
confidence: 99%
“…In contrast, modeling KHLH7 mutations that are implicated in Crisponi and BOS3, c.1115G > A:p.(Arg372Gln) and c.1258C > T:p.(Arg420Cys), revealed that they were localized to the Kelch domain (Figure 5b pink circles) [1215]. More specifically, these arginine amino acids were located at structurally analogous positions in blades III and IV within the inter-blade loop.…”
Section: Resultsmentioning
confidence: 99%
“…Structural analysis of the variants seen in our cohort when compared to reported recessive loss-of-function alleles suggests a domain-dependent correlation between genotype and phenotype. Mutations in the 3-box motif of the BACK domain appear to cause interruptions to the assembly of Cul3 ligase, and, consequently, the UPP degradation pathway in a dominant negative fashion [ 6, 7, 10, 13, 15]. Interruptions of the UPP degradation pathway have been implicated in other genetic etiologies of RP, such as TOPORS mediated adRP and the p.Pro23His variant in RHO mediated adRP [32].…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17] Regarding the variants of KLHL7, only 13 have been identified in 21 patients so far, two of whom participated in the present study. [11][12][13][18][19][20][21] In this study, we present the molecular basis of CS/CISS-like phenotypes in 23 clinically well-characterized patients, combining data gathered from two centers in Turkey. This report expands the clinical and molecular spectrum of CRLF1 and KLHL7-related disorders.…”
mentioning
confidence: 99%
“…Stepwise targeted Sanger sequencing had been applied initiating with the CRLF1 gene (NM_004750.5) and followed with the CLCF1 gene (NM_013246.3) for patients with classical CS/CISS findings and the KLHL7 gene (NM_001031710.3) was screened for patients with CS/CISS-like phenotype (Supplement Table 1). Proband of one family had been molecularly investigated by whole-exome sequencing at an external center with a large cohort of arthrogryposis and his variant was previously published (proband BAB10699 in reference 19). Clin-Var database 22 and comprehensive literature search were used for variant analysis.…”
mentioning
confidence: 99%